Investigating the Determinants of Shariah-Compliant Firms Profitability in Indonesia: Does COVID-19 Play an Essential Role? - Mohammad Bintang Pamuncak; Arland Pratama Wijaya (AL-MUZARA'AH, 2022)
This study aims to seek the determinants of sharia-compliant firm profitability in Indonesian JII listed companies. This study employed Data Panel regression analysis using the 12 most consistent companies who listed in the JII during the period of Q1 2015 to Q4 2020 where in total, there are 282 number of observation. The study found that both firm-internal and firm-external variabels are significant in determining firm profitability on at least one model of data panel regression. COVID-19 and GDP used to measure the impact of firm-external variables, while working capital, debt to equity ratio, and quick ratio used to determine firm-internal variable. Further studies are required to observe the longer period of COVID-19 impact on sharia-compliant firm profitability.